Guidelines Against Discrimination and Bias in Anatomical Research Papers (GDBARP): Recommendations From Anatomical Journal Editors - Iwanaga, Joe; Takeda, Sén; Walocha, Jerzy A.; Ribatti, Domenico; del Sol, Mariano; Ravi, Kumar Satish; Moryś, Janusz; Paulsen, Friedrich; Singh, Vishram; Apaydin, Nihal; Kim, Hee Jin; Adds, Philip; et al. (Clinical Anatomy, 2025)
Most discussions about discrimination and bias in anatomical research papers have been limited to terminology relating to race/ethnicity and gender/sex. However, as editors of anatomical journals, the authors of this article have frequently observed broader instances of potential discrimination and bias within anatomical research. These often stem from differences among authors' backgrounds, traditions, cultures, religions, provenance/origins, and workplace affiliations. In view of the limited discourse on this topic, we seek in this article to establish a consensus among editors of anatomical journals and to propose new Guidelines Against Discrimination and Bias in Anatomical Research Papers (GDBARP). We have identified multiple factors that can contribute to discrimination and bias, underscoring the need for greater awareness and proactive measures. It is imperative in anatomical research to respect authors, reviewers, and editors regardless of their background, culture, traditions, sex, ethnicity, language, religion, or ethical perspectives.
CRIS-Team Scopus Importer:2025-05-30
Keywords: anatomy; bias; cadavers; discrimination; dissection; medical ethics; prejudice; recommendation; research; terminology